RPA-assisted CRISPR-Cas12a-enabled point-of-care diagnostic platform for chili leaf curl virus with fluorescent and colorimetric readouts - Paul, Samrat; Emmadi, Venu; Saxena, Shipra; Sarkar, Mehulee; Mandal, Bikash; Kumar, Ravinder; Sinha, Parimal; Roy, Anirban (Frontiers in Microbiology, 2025)
Chili leaf curl virus (ChiLCV) is a highly destructive begomovirus that causes significant economic losses in chili production across the Indian subcontinent. Accurate detection of the virus is crucial for effective disease management. This study presents a Recombinase Polymerase Amplification (RPA)-assisted DNA endonuclease-targeted CRISPR trans reporter (DETECTR) system for the rapid, highly sensitive, and specific detection of ChiLCV, specifically targeting the AC1 gene sequence. A crRNA specific to AC1 gene of ChiLCV- was designed, and the RPA conditions were optimized. The detection method involves cleaving a tagged oligo reporter (Fluorophore-quencher or Biotin-FAM), allowing results to be visualized via either a fluorescence read-out-based assay or a Lateral Flow Assay (LFA) with gold nanoparticles conjugated to FAM antibody. We standardized the critical concentration of the biotin-FAM oligo reporter such that, in the presence of the viral genome, the activated CRISPR-Cas12a cleaves all reporters, resulting in a dark test line on the lateral flow strip. This RPA-assisted fluorescence or LFA readout-based DETECTR system demonstrates exceptional specificity and sensitivity, detecting ChiLCV at a concentration as low as 7 femtograms when using cloned plasmid DNA, comparable to the gold standard detection method, like real-time PCR. The system successfully detected the virus in crude leaf extracts from infected plants while distinguishing ChiLCV from related begomoviruses and damage caused by common pests like mites and thrips. The DETECTR system was finally validated with field infected samples collected from major chili-growing states of India. To the best of our knowledge, this is the first demonstration of a CRISPR-based assay for ChiLCV that can be applied directly to crude leaf extracts, thereby enhancing its potential utility in point-of-care diagnostics. A key advantage of this diagnostic approach is its rapid processing time and field applicability, making it an accessible and practical tool for farmers and agricultural specialists to implement timely virus disease management strategies for chili crops.